2019
DOI: 10.1111/1753-6405.12912
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for sport organisations developing and delivering non‐traditional social sport products for insufficiently active populations

Abstract: Objectives:To explore the challenges that Victorian sporting organisations experience when developing, delivering or scaling non-traditional social sport products to engage insufficiently active people. Methods: Online ConceptMapping was used to gather qualitative data and analyse it quantitatively.Results: A total of 68 participants (27 organisations) brainstormed 158 challenges. The research team synthesised these to 71 unique challenges for participants to sort into groups and rate for importance (0-5) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…To effectively retain these population groups in sport, Hockey NSW (and all sports) should adapt elements of their sport delivery. Staley et al (2019) suggests sports should recruit appropriate product deliverers, build the capacity of the delivery organisation, and develop relevant social sport products which align with the specific needs and characteristics of the target groups [ 26 ]. For example, Peralta, Cinelli (28) conducted a sport-based mentoring program with remote Aboriginal communities in Australia.…”
Section: Discussionmentioning
confidence: 99%
“…To effectively retain these population groups in sport, Hockey NSW (and all sports) should adapt elements of their sport delivery. Staley et al (2019) suggests sports should recruit appropriate product deliverers, build the capacity of the delivery organisation, and develop relevant social sport products which align with the specific needs and characteristics of the target groups [ 26 ]. For example, Peralta, Cinelli (28) conducted a sport-based mentoring program with remote Aboriginal communities in Australia.…”
Section: Discussionmentioning
confidence: 99%
“…A major barrier to reducing physical inactivity is the initial engagement and reach to recruit key inactive groups [5,20]. The targeted approach of the Move It AUS grants were based on findings reported by both GAPPA, and through Sport Australia's AusPlay data, which identified key inactive population groups [4,6].…”
Section: Discussionmentioning
confidence: 99%
“…Casey et al (2011) made the case for long-term commitments in funding strategies and partnerships to provide sustainability, which was echoed from program providers concerned about resources required to maintain delivery [28]. Similarly, Staley et al (2019) found that addressing inactivity through sport requires collaboration and support across multiple levels of the ecosystem [20]. Crosssectoral collaboration is instrumental in reaching specific inactive target groups and should be embedded in future initiatives to support sustained delivery and fair access to sport and PA opportunities across the lifespan [2,5,28,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research is oriented to produce a product (Sugiyono, 2013). Research and development is generally based on a new product or a method developed from the limitations of previous researchers to make it simpler or more interesting and accountable (Flynn et al, 2020;Staley et al, 2019). This study uses Brog & Gall steps with a 10-step approach.…”
Section: Methodsmentioning
confidence: 99%